2004
DOI: 10.1002/jmri.20010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional fast spin echo, single‐shot two‐dimensional and three‐dimensional half‐fourier RARE for T2‐weighted female pelvic imaging

Abstract: Purpose:To evaluate the usefulness of the three-dimensional half-Fourier RARE sequence in comparison with single-shot two-dimensional half-Fourier RARE and conventional fast spin echo (FSE) for female pelvic imaging. Materials and Methods:Imaging with all sequences was performed in 146 patients with 166 focal lesions on a 1.5-T system. The images were compared on the basis of quality, lesion conspicuity, and lesion to the uterus contrast-tonoise ratio (CNR). Results:The sharpness of intrapelvic organs on the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Instead, SSFSE sequences may be used to obtain relatively motion-free breath-hold sequences with tissue contrast similar to that obtained when using more conventional fast spin-echo T2-weighted images [23]. The drawback of this sequence is the inherently low signal-tonoise ratio (SNR) and contrast-to-noise ratio (CNR) in the uterus [23,24]. Therefore, Nakai et al examined the optimal scan interval for the evaluation of uterine peristalsis and the best performance was obtained with a 4-s scan interval, which yielded a superior CNR and peristaltic detection compared with the 2-or 3-s scan intervals [25].…”
Section: Subtle and Rhythmic Uterine Contractions: Uterine Peristalsimentioning
confidence: 99%
“…Instead, SSFSE sequences may be used to obtain relatively motion-free breath-hold sequences with tissue contrast similar to that obtained when using more conventional fast spin-echo T2-weighted images [23]. The drawback of this sequence is the inherently low signal-tonoise ratio (SNR) and contrast-to-noise ratio (CNR) in the uterus [23,24]. Therefore, Nakai et al examined the optimal scan interval for the evaluation of uterine peristalsis and the best performance was obtained with a 4-s scan interval, which yielded a superior CNR and peristaltic detection compared with the 2-or 3-s scan intervals [25].…”
Section: Subtle and Rhythmic Uterine Contractions: Uterine Peristalsimentioning
confidence: 99%
“…There are two potentially opposing factors that need to be considered when selecting an appropriate interscan delay for cine MRI. The 2D SSFSE sequence has an inherently low signal‐to‐noise ratio (SNR) and contrast‐to‐noise ratio (CNR) in the uterus . Cine MR images acquired with a short scan interval result in progressive tissue saturation from incomplete signal recovery and reduce SNR and CNR .…”
mentioning
confidence: 99%
“…Studies have been conducted to compare 2D and 3D half-Fourier TSE sequences with standard 2D T2-weighted TSE sequences in MRI of the female pelvis. These studies [7][8][9] showed good image quality and improved time efficiency with the 2D half-Fourier TSE sequence and higher contrast, improved time efficiency, and superior through-plane resolution (2-3 mm) with the 3D half-Fourier TSE sequence. However, no attempt was made in those studies to generate multiplanar reconstructions of the 3D source data sets because the slice thickness of 2-3 mm seemed insufficient for acquisition of reformations of high quality.…”
Section: Discussionmentioning
confidence: 89%